Analysis of aquaporin 9 expression in human epidermis and cultured keratinocytes. Issue 1 (26th June 2014) - Sugiyama, Yoshinori; Yamazaki, Kohei; Kusaka-Kikushima, Ayumi; Nakahigashi, Kyoko; Hagiwara, Hiromi; Miyachi, Yoshiki
Abstract : Aquaporin 9 (AQP9) is a member of the aquaglyceroporin family that transports glycerol, urea and other small solutes as well as water. Compared to the expression and function in epidermal keratinocytes of AQP3, another aquaglyceroporin, our knowledge of epidermal AQP9 remains elusive. In this study, we investigated the expression of AQP9 in the human epidermis and cultured keratinocytes. Immunofluorescence studies revealed that AQP9 expression is highly restricted to the stratum granulosum of the human epidermis, where occludin is also expressed at the tight junctions. Interestingly, the AQP3 staining decreased sharply below the cell layers in which AQP9 is expressed. In cultured normal human epidermal keratinocytes (NHEK), knock‐down of AQP9 expression in the differentiated cells induced by RNA interference reduced glycerol uptake, which was not as pronounced as was the case with AQP3 knock‐down cells. In contrast, similar reduction of urea uptake was detected in AQP9 and AQP3 knock‐down cells. These findings suggested that AQP9 expression in NHEK facilitates at least the transport of glycerol and urea. Finally, we analyzed the effect of retinoic acid (RA), a potent stimulator of keratinocyte proliferation, on AQP3 and AQP9 mRNA expression in differentiated NHEK. Stimulation with RA at 1 μM for 24 h augmented AQP3 expression and down‐regulated AQP9 expression. Collectively, these results indicate that AQP9 expression in epidermal keratinocytes is regulated in a different manner from that of AQP3. Abstract : AQP9 is expressed in the upper layer of the stratum granulosum of human epidermis. AQP9 expressed in keratinocytes facilitates glycerol and urea transportation. Retinoic acid down‐regulates AQP9 mRNA expression in differentiated keratinocytes.